2018
DOI: 10.1002/admi.201801297
|View full text |Cite
|
Sign up to set email alerts
|

A New Graphitic Carbon Nitride/Horseradish Peroxidase Hybrid Nano–Bio Artificial Catalytic System for Unselective Degradation of Persistent Phenolic Pollutants

Abstract: It has always been a challenge to fabricate artificial catalytic system as one promising strategy of using solar energy for chemical synthesis, fuel production, electrochemical detection, pollutant degradation, etc. Here a new g‐C3N4/horseradish peroxidase hybrid nano–bio artificial catalytic system is exploited. The coupling effect between photocatalysis and biocatalysis cycles not only forcefully improves the separation efficiency of charge carriers but also continuously produces more OH active species, fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 35 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…Recently, graphitic carbon nitride (g-C 3 N 4 ) have been stimulated keen research interest in the photocatalytic degradation of pollutants, photocatalytic hydrogen production, carbon dioxide reduction, and disinfection because of its unique 2D layered structure, excellent chemical stability, and tunable electronic structure. [24][25][26][27] Nevertheless, the photocatalytic activity of pure g-C 3 N 4 is far from satisfaction, which is mainly due to the low-specific surface area and the rapid recombination of photogenerated electron-hole pairs. [28][29][30][31] In the context, various methods are proposed to enhance the photocatalytic performance of g-C 3 N 4 containing increasing specific surface area, morphology control, element doping, heterostructure construction, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graphitic carbon nitride (g-C 3 N 4 ) have been stimulated keen research interest in the photocatalytic degradation of pollutants, photocatalytic hydrogen production, carbon dioxide reduction, and disinfection because of its unique 2D layered structure, excellent chemical stability, and tunable electronic structure. [24][25][26][27] Nevertheless, the photocatalytic activity of pure g-C 3 N 4 is far from satisfaction, which is mainly due to the low-specific surface area and the rapid recombination of photogenerated electron-hole pairs. [28][29][30][31] In the context, various methods are proposed to enhance the photocatalytic performance of g-C 3 N 4 containing increasing specific surface area, morphology control, element doping, heterostructure construction, etc.…”
Section: Introductionmentioning
confidence: 99%
“…cence lifetime of MoO 3−x -PCN-2 (5.917 ns) was much longer than that of the bulk PCN sample (5.017 ns). This result suggested that the efficient electron/hole pairs separation had been realized after the suitable amount of MoO 3−x species loading [38]. Longer fluorescence lifetime than bulk PCN could also be observed for other MoO 3−x -PCN-X samples (FIG.…”
Section: Resultsmentioning
confidence: 79%
“…XRD is first carried out to identify the phases and structures of the samples. As shown in Figure , the XRD patterns of the original g-C 3 N 4 sample shows two characteristic diffraction peaks at 13.1° and 27.6° that belong to (100) lattice planes of triazine units and (002) lattice planes of interlayer stacking of aromatic segments, respectively, which implies that the pure g-C 3 N 4 sample was obtained . By comparison, a weak diffraction peak also appears at 40.9° in the XRD pattern of the NiCoP/g-C 3 N 4 -3 sample beside the strongest diffraction peak of g-C 3 N 4 , which corresponds exactly to the (111) lattice planes of NiCoP (PDF# 71-2336), indicating the successful modification of NiCoP nanoclusters on 2D g-C 3 N 4 nanosheets.…”
Section: Resultsmentioning
confidence: 92%
“…As shown in Figure 1, the XRD patterns of the original g-C 3 N 4 sample shows two characteristic diffraction peaks at 13.1°and 27.6°that belong to (100) lattice planes of triazine units and (002) lattice planes of interlayer stacking of aromatic segments, respectively, which implies that the pure g-C 3 N 4 sample was obtained. 28 3d), the weak peak at 129.3 eV is ascribed to Ni δ+ −P δ− and Co δ+ −P δ− bonding states in NiCoP, while the peak at 133.4 eV stems from the surficial oxidized P species. 33,34 Furthermore, the Co 2p XPS spectrum shown in Figure 3e illustrates that one peak at 778.1 eV originates from the 2p 3/2 state of Co δ+ (0 < δ < 2) atoms in NiCoP, whereas the three peaks at 781.4, 783.0, and 784.4 eV are assigned to surficial oxidized Co species, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%